Flow scheduling technology based on BGP extended protocol - Yujia LUO; Liang OU; Zhiwei MO; Hong TANG (Dianxin kexue)
A novel centralized flow scheduling scheme based on software defined networking（SDN）was proposed.The existing problems of current flow scheduling method based on BGP were analyzed，and a new scheme was proposed.In the scheme，the BGP Flowspec was enhanced to avoid reconfiguring the related routers one by one，and hence the network management was simplified and a more flexible flow scheduling method was provided.The proposed scheduling scheme is compatible with the traditional BGP，which matches the trend of current industry and solves some of the problems in traditional BGP scheme.